2013
DOI: 10.5152/balkanmedj.2012.075
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Evaluation of Intensity Modulated Radiotherapy and 4-Field 3-D Conformal Radiotherapy in Prostate Cancer Treatment

Abstract: Objective: Dexmedetomidine has been reported to produce analgesia after intrathecal administration. In the present study the α2-adrenoceptor agonist dexmedetomidine was evaluated for its potential spinal neurotoxic effects.Material and Methods: Three days after intrathecal cannulation, rats were administered either dexmedetomidine (3 μg/30 μL, i.t.) or saline (30 μL, i.t.). Antinociceptive, sedative and motor effects of intrathecal administrations of dexmedetomidine or saline were evaluated during 90 min. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
3
11
1
Order By: Relevance
“…IMRT with 6 and 15-MV had better protection for both femoral heads compared to that for 3D-CRT in both 6 and 15-MV photons. The present study is consistent with an article by Uysal et al [23] who concluded that the mean dose to right head of femur was 31.95 Gy in 3D-CRT and 17.98 Gy in IMRT and the mean dose to left head of femur was 31.5 Gy 18.79 Gy in 3D-CRT vs. IMRT respectively and consistent with other studies by Reddy et al [24]. When comparing low energy (3D-CRT 6-MV) vs. high energy (3D-CRT 15-MV) in terms of OARs, 3D-CRT 15-MV was slightly superior in sparing bladder and both femoral heads compared to 3D-CRT 6-MV and the differences were statistically significant.…”
Section: D-crtsupporting
confidence: 94%
“…IMRT with 6 and 15-MV had better protection for both femoral heads compared to that for 3D-CRT in both 6 and 15-MV photons. The present study is consistent with an article by Uysal et al [23] who concluded that the mean dose to right head of femur was 31.95 Gy in 3D-CRT and 17.98 Gy in IMRT and the mean dose to left head of femur was 31.5 Gy 18.79 Gy in 3D-CRT vs. IMRT respectively and consistent with other studies by Reddy et al [24]. When comparing low energy (3D-CRT 6-MV) vs. high energy (3D-CRT 15-MV) in terms of OARs, 3D-CRT 15-MV was slightly superior in sparing bladder and both femoral heads compared to 3D-CRT 6-MV and the differences were statistically significant.…”
Section: D-crtsupporting
confidence: 94%
“…The doses to both femora and that to penile bulb in favour of IMRT revealed high statistically significant difference, whereas the P values were 0.001 and 0.009, respectively. In a similar study, Uysal et al 15 compared between IMRT and 3D-CRT dosimetric plans for a 68 Gy dose in 20 patients with low/moderate risk prostate cancer. They found a statistically significant better target organ dose homogeneity with the 7-field IMRT plan (<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Arc Modulation Optimization Algorithm (AMOA) has been utilized for optimization of target volume coverage and critical organ sparing. SBRT [38][39][40][41][42][43][44] .…”
Section: Treatmentmentioning
confidence: 99%